2016
DOI: 10.1016/j.jad.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal psychotherapy as add-on for treatment-resistant depression: A pragmatic randomized controlled trial

Abstract: ClinicalTrials.gov-NCT01896349.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…This appeared acceptable to participants receiving ISTDP in that only 1 person requested antidepressant augmentation during treatment and, compared to TAU, significantly more participants stopped or reduced medications during treatment. Furthermore, the 36% full remission rates at the end of ISTDP in the Halifax Study is comparable to the remission rates reported in other trials (21.0-38.5%) (Kocsis et al, 2009;Souza et al, 2016;Thase et al, 2007;Wiles et al, 2013). To test the effectiveness of ISTDP as an augmentation strategy for TRD it should be delivered alongside antidepressants and compared against a control group receiving the same medication algorithm.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…This appeared acceptable to participants receiving ISTDP in that only 1 person requested antidepressant augmentation during treatment and, compared to TAU, significantly more participants stopped or reduced medications during treatment. Furthermore, the 36% full remission rates at the end of ISTDP in the Halifax Study is comparable to the remission rates reported in other trials (21.0-38.5%) (Kocsis et al, 2009;Souza et al, 2016;Thase et al, 2007;Wiles et al, 2013). To test the effectiveness of ISTDP as an augmentation strategy for TRD it should be delivered alongside antidepressants and compared against a control group receiving the same medication algorithm.…”
Section: Discussionmentioning
confidence: 52%
“…Like other recent psychotherapy trials (Souza et al, 2016;Wiles et al, 2013), we chose this pragmatic definition to be representative of a heterogeneous and difficult-to-treat population commonly requesting care at secondary care CMHTs. While there is no standard universally accepted definition or criteria of TRD, the number and type of prior antidepressant medication failures may be considered an indication of degree of TRD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRISMA flow chart describing the inclusion process is presented in Figure . A total of 101 studies met inclusion criteria (11,910 participants overall: 2,587 randomized to combined treatment, 3,625 to psychotherapy, 4,769 to pharmacotherapy, 632 to placebo and 297 to psychotherapy plus placebo).…”
Section: Resultsmentioning
confidence: 99%
“…This requires that Chinese teachers do not only teach basic language knowledge but also pragmatic analysis of language environment, language knowledge, and cultural background. In practical teaching, it is necessary not only to explicitly put forward the teaching goal of improving students' pragmatic competence, but also to implement this goal in all aspects of practical teaching [3]. Language training mode is as follows.…”
Section: Application In Classroom Teachingmentioning
confidence: 99%